PENGARUH PENGALAMAN, BEBAN KERJA, DAN PELATIHAN TERHADAP SKEPTISME DAN KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (Studi Empiris Pada Auditor di BPKP Perwakilan Provinsi Riau) - Ulfa Novita; Andreas -; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was aimed to examine the direct effect of audit experience, workload, training and skepticism to fraud detection ability of auditors, and also indirect effect of audit experience, workload, and training to fraud detection ability of auditors with skepticism as intervening variables. Collecting data of this study using a questionnaire submitted auditors who work at Badan Pengawasan Keuangan dan Pembangunan (BPKP) Riau Province Representation. A total respondents used in this research is 48 respondents. Data analysis for hypothesis test was done with Partial Least Square (PLS). Result of this study give evidence that experience, workload, and training have significantly effect toward skepticism; training and skepticism have direct effect toward fraud detection ability of auditors, didn’t find direct effect of experience and workload toward fraud detection ability of auditors; experience, workload, and training have indirect effect toward fraud detection ability of auditors through skepticismKeywords: experience, workload, training, professional skepticism, and fraud detection ability of auditors